Triplet Pregnancy With a Complete Hydatidiform Mole Co-Existing With Two Fetuses [15K]. (May 2016) - Farag, Sara; Saltzman, Daniel; Fox, Nathan; Klauser, Chad; Rebarber, Andrei; Gupta, Simi
Abstract : INTRODUCTION: Triplet pregnancies with a hydatidiform mole and two co-existing fetuses (HMTCF) are rare, mostly resulting from infertility treatments. METHODS: This is a case of a 30 year old Caucasian G1P0 with infertility who underwent successful in vitro fertilization with a three-embryo transfer resulting in a triplet gestation of a HMTCF. RESULTS: The patient experienced preterm labor with bleeding and subsequent delivery of live twins at 26 weeks via cesarean. Her Beta HCG levels dropped appropriately and she had a normal postpartum course. CONCLUSION: The outcomes vary amongst reported cases: 32% terminated electively or due to maternal complications; 9% had spontaneous abortions; and 59% delivered vaginally or by cesarean delivery, for whom the average gestational age at delivery was 29±5 weeks. Of the pregnancies that were allowed to continue, 60% resulted in one or more live twin births. Antepartum complications included vaginal bleeding (55%), pre-eclampsia (23%), hyperemesis gravidarum (14%), hyperthyroidism (9%), and persistent gestational trophoblastic disease (41%). Patients with HMTCF should be counseled about the risks of such a pregnancy.